Repetisi dan Fungsinya dalam Novel Di Tanah Lada Karya Ziggy Zezsyazeoviennazabrizkie: Analisis Stilistika - Pamungkas, Sidiq Aji; Saddono, Kundharu (METASASTRA: Jurnal Penelitian Sastra, 2018)
This research aims to describe repetition and its function in Ziggy’s “Di Tanah Lada”. The research applies a qualitative descriptive approach with content analysis strategy to discuss linguistic phenomenon in novel, especially repetition as a figure of speech. The technique of collecting data is literary study and interview. Data validity is triangulation theory and source of data triangulation. The writer applies Keraf’s, Al-Maruf’s, and Nurgiyantoro’s language style theory. The research uses a purposive sampling. The result of the research indicates two findings. First, the repetition used by Ziggy in “Di Tanah Lada” novel includes anaphora, mesodiplosis, tautotes, and anadiplosis. Second, the repetition used by Ziggy describes the character’s feeling, clarifies the meaning, and gives a certain atmosphere and impressions.